High-resolution magnetic resonance vessel wall imaging provides new insights into Moyamoya disease - Yang, Hui; Huang, Guilan; Li, Xi; Wu, Moxin; Zhou, Weixin; Yin, Xiaoping; Zhang, Manqing; Chen, Zhiying (Frontiers in Neuroscience, 2024)
Moyamoya disease (MMD) is a rare condition that affects the blood vessels of the central nervous system. This cerebrovascular disease is characterized by progressive narrowing and blockage of the internal carotid, middle cerebral, and anterior cerebral arteries, which results in the formation of a compensatory fragile vascular network. Currently, digital subtraction angiography (DSA) is considered the gold standard in diagnosing MMD. However, this diagnostic technique is invasive and may not be suitable for all patients. Hence, non-invasive imaging methods such as computed tomography angiography (CTA) and magnetic resonance angiography (MRA) are often used. However, these methods may have less reliable diagnostic results. Therefore, High-Resolution Magnetic Resonance Vessel Wall Imaging (HR-VWI) has emerged as the most accurate method for observing and analyzing arterial wall structure. It enhances the resolution of arterial walls and enables quantitative and qualitative analysis of plaque, facilitating the identification of atherosclerotic lesions, vascular entrapment, myofibrillar dysplasia, moyamoya vasculopathy, and other related conditions. Consequently, HR-VWI provides a new and more reliable evaluation criterion for diagnosing vascular lesions in patients with Moyamoya disease.